Characterization of Tool Wear in High-Speed Milling of Hardened Powder Metallurgical Steels. (20th November 2011) - Klocke, Fritz; Arntz, Kristian; Cabral, Gustavo Francisco; Stolorz, Martin; Busch, Marc
Abstract : In this experimental study, the cutting performance of ball-end mills in high-speed dry-hard milling of powder metallurgical steels was investigated. The cutting performance of the milling tools was mainly evaluated in terms of cutting length, tool wear, and cutting forces. Two different types of hardened steels were machined, the cold working steel HS 4-2-4 PM (K490 Microclean/66 HRC) and the high speed steel HS 6-5-3 PM (S790 Microclean/64 HRC). The milling tests were performed at effective cutting speeds of 225, 300, and 400 m/min with a four fluted solid carbide ball-end mill (D 0 = 6, TiAlN coating). It was observed that by means of analytically optimised chipping parameters and increased cutting speed, the tool life can be drastically enhanced. Further, in machining the harder material HS 4-2-4 PM, the tool life is up to three times in regard to the less harder material HS 6-5-3 PM. Thus, it can be assumed that not only the hardness of the material to be machined plays a vital role for the high-speed dry-hard cutting performance, but also the microstructure and thermal characteristics of the investigated powder metallurgical steels in their hardened state.